PENGARUH KONSENTRASI POC DAUN KELOR DAN JENIS MEDIA TUMBUH TERHADAP PERTUMBUHAN SERTA HASIL TANAMAN SELADA ROMAINE (Lactuca sativa var. longifolia) SECARA HIDROPONIK NFT - Beni Andika; Mardaleni (DINAMIKA PERTANIAN, 2025)
This research aims to determine the interaction of Moringa leaf POC concentration and type of growing media on the growth and yield of romaine lettuce (Lactuca sativa var. longifolia) using NFT hydroponics. This research was conducted at the Greenhouse of Riau Islamic University's UPT from December 2023 to February 2024. This research used a Divided Plot Design (RPT) in RAL. The first factor was the concentration of liquid organic fertilizer from Moringa leaves (D), with four treatment levels: 200 ppm, 400 ppm, 600 ppm, and 800 ppm. The second factor was the growing medium, with four treatment levels: rockwool, cocopeat, husk charcoal, and wood biochar. The parameters observed were plant height, number of leaves, chlorophyll content, plant fresh weight, root volume, plant dry weight, and root-shoot ratio. The data were analyzed statistically and followed by the honest real difference test (BNJ) at the 5% level. The research results showed that the interaction between the concentration of liquid organic fertilizer from Moringa leaves and the growing medium was significant for plant height, number of leaves, chlorophyll content, plant fresh weight, root volume, plant dry weight, and root-shoot ratio. All romaine lettuce plant parameters observed in this study yielded the best results at a concentration of 200 ppm liquid organic fertilizer (POC) from Moringa leaves and rockwool growing media.